Arene ruthenium, rhodium and iridium complexes containing N∩O chelating ligands: synthesis, antibacterial and antioxidant studies. Issue 14 (18th July 2021) - Lapasam, Agreeda; Shadap, Lathewdeipor; Tripathi, Deepak Kumar; Poluri, Krishna Mohan; Kaminsky, Werner; Kollipara, Mohan Rao
Abstract: The reaction of [(arene)MCl2 ]2 with ligands 4-hydroxy-benzhydrazide (L1) and 3-methoxy-benzhydrazide (L2) leads to formation of cationic complexes 1 -6 having the general formula [(arene)M(L)Cl] + {arene = p -cymene, M = Ru; arene = Cp*; M = Rh/Ir; L = L1 and L2}. The reaction of [CpRu(PPh3 )2 Cl] with L1 and L2 yielded cationic complexes that have been formulated as [CpRu(L)PPh3 ]Y {Y = Cl (7 ), Y = PF6 (8 )}. The molecular structures of 1, 2 and 4 revealed that these complexes adopt typical three-legged "piano stool" geometry. The arene ring occupies the apex of the stool, terminal chloride and N, O-bidentate ligands are coordinated to the metal center at the base of the stool. The antibacterial activity of the ligands and complexes was evaluated on Gram-positive S. aureus, B. thuringiensis and Gram-negative E. coli, P. aeruginosa strains; some complexes exhibit moderate antibacterial activity towards gram-positive bacteria. The antioxidant studies of these complexes have been carried out, and the results showed that these complexes have strong DPPH-scavenging properties. Graphical Abstract: UF0001